Stability of geosynthetic reinforced embankments over stone column-improved soft soil - Labed, Mohamed; Mellas, Mekki (Journal of Applied Engineering Science & Technology; Vol 2 No 2 (2016), 2016)
The stability of embankments on soft soils is a common problem; the reinforcement of this type of soil by a geosynthetic sheet above stone columns is a recent technique, for an excellent distribution of the vertical stresses on the stone columns and the soft soils. This paper focuses on the numerical analysis of a geosynthetic-reinforced embankment over stone column-improved soft soil. The finite difference code Fast Lagrangian Analysis of Continua in 3 Dimensions (FLAC3D) was used to determine the optimal placement of the geosynthetic sheet. The embankment fill, the subsoil, and the stone columns were modeled by an elasto-plastic model with a Mohr-Coulomb yield criterion and associated flow rule. In this study, several geometrical and mechanical parameters have been considered, such as the stiffness modulus, the placement of geosynthetic sheet, and the internal friction angle of the embankment fill. The factor of safety obtained by 3D numerical method was compared with those obtained by 2D numerical methods. The results of this study show the effect of the placement and stiffness of the geosynthetic sheet on the factor of safety.
Keywords: Geosynthetic; Stone column; Finite difference; Stability; Factor of safety; Embankment